Chassis Structural Design of Track Racing One Manned Formula Car - W. Lim, J; Sivaguru, S (International Journal of Engineering and Technology, 2018)
The current work contains the design and optimisation of a spaceframe chassis for a track racing one manned formula car able to participate in the Formula Society of Automotive Engineers (Formula SAE) 2017/2018. Materials, profile cross section types were selected by considering the theories of elastic failure. The structural strength of the chassis was determined by Finite Element Analysis using ABAQUS software by determining the stress distribution during static and dynamic loading in addition to exposing the modal frequencies. Beam elements were used in the finite element model as it provides accurate modelling of small deflection bending responses. A simple baseline chassis design was developed that adheres to the Formula SAE 2017/2018 rules. Optimisations were made in terms of the configuration and material utilisation of the chassis members were done to prevent yielding during the static loading of car components and dynamic loading during acceleration and cornering. Furthermore, the same method of optimisation was used in prevention of the coincidence of natural frequency with the frequency of the engine.Â Â